2014
DOI: 10.1002/pat.3311
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of serum proteins and alkaline phosphatase with poly(styrene/α‐tert‐butoxy‐ω‐vinylbenzyl‐polyglycidol) microspheres with various surface concentrations of polyglycidol

Abstract: Interactions of human serum albumin, gamma globulins and alkaline phosphatase with surface of hydrophilic microspheres are described. Relation between the composition of particles surface layer and adsorption/covalent immobilization and activity of proteins is elucidated. The set of poly(styrene/α‐tert‐butoxy‐ω‐vinylbenzyl‐polyglycidol) microspheres (poly(S/PGly)) was synthesized via emulsion copolymerization of styrene and α‐tert‐butoxy‐ω‐vinylbenzyl‐polyglycidol (PGL) macromonomer (Mn = 3000, Mw/Mn = 1.08). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…weight of c-globulins equal 160 kDa, the dimensions 23/2.5/2.5 nm and assuming their vertical orientation with contracted F(ab) fragment [25]. Data in Table 2 indicate that in some cases the degree of coverage exceeds 100 %, suggesting formation of a protein layer thicker than the monolayer.…”
Section: Adsorption Of C-globulinsmentioning
confidence: 91%
See 1 more Smart Citation
“…weight of c-globulins equal 160 kDa, the dimensions 23/2.5/2.5 nm and assuming their vertical orientation with contracted F(ab) fragment [25]. Data in Table 2 indicate that in some cases the degree of coverage exceeds 100 %, suggesting formation of a protein layer thicker than the monolayer.…”
Section: Adsorption Of C-globulinsmentioning
confidence: 91%
“…These proteins were selected for the studies because they are well defined and show a high affinity to surfaces of many materials [22][23][24][25]. They are often used in studies of protein adsorption [22,[24][25][26]. Gamma globulins are present in biological fluids where they play important physiological roles [27].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hydrophilic or hydrophobic [31] polymers on a particle's surface creates opportunities for specific applications. Moreover, shell-building polymers can exhibit specific properties, such as thermosensitivity in the case of PNIPAM [30] and PNVIBA, antifouling behaviour of poly(ethylene glycol) (PEG) [32,33] and polyglycidol [22] or conductivity in the case of polypyrrole [4,34] and polyaniline [35]. To examine the surface composition, direct and indirect methods can be applied.…”
Section: Methods Of Particle Surface Analysismentioning
confidence: 99%
“…It has been shown that an increase in the molar fraction of polyglycidol macromonomer during synthesis resulted in the increased amount of polyglycidol fraction in the surface. The authors also examined the influence of changes in the particles' synthesis conditions, namely from batch (all reagents introduced from the beginning of the process) to continuous (polyglycidol macromonomer was added in a continuous manner to the reaction mixture) polymerization [22].…”
Section: Methods Of Particle Surface Analysismentioning
confidence: 99%
See 1 more Smart Citation